The Description of Student's Mathematical Communication Skills in Solving Circle Problems in Term of Learning Style - Suradi Tahmir; Sahid Sahid; Erjun D. (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2022)
This research aims to find out the description of a student's mathematical communication skills in solving circle problems, judging from learning style. The type of research used is qualitative research with a descriptive approach.There are six research subjects namely, two visual learning style students, two auditorial learning style students, and two kinesthetic learning style students. The main instrument in this research is the researcher and supporting instruments used are written test instruments and interview guidelines. Data collection techniques in this study are tests and interviews. Data analysis techniques were used, namely data condensation, data presentation, and drawing conclusions. The results showed that subjects with visual learning styles were able to meet all indicators of mathematical communication ability while subjects with auditory learning styles and kinesthetic learning styles were only able to meet 3 of 5 indicators of mathematical communication ability.